Wireless Instrumentation: the New Frontier - Nechibvute, Action; Mudzingwa, Courage (2016)
Wireless Sensor Networks (WSNs) are an emerging technology that is being gradually adopted in industrial process automation due to its potential benefits such as increased network flexibility, mobility, and cost reduction. WSN technologies have merged with the traditional industrial field instrumentation into an exciting new technology of wireless instrumentation, which is an appealing development in industrial process since the recent approvals of the WirelessHART and ISA100.11a standards. This article gives an overview of wireless instrumentation, including the potential benefits, challenges and future research development of the wireless instrumentation as a new frontier in modern industrial automation.